2020
DOI: 10.1098/rstb.2019.0649
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat concentrations influence fatty acid assimilation patterns in Atlantic pollock (Pollachius virens)

Abstract: A key aspect in the use of fatty acids (FA) to estimate predator diets using quantitative FA signature analysis (QFASA) is the ability to account for FA assimilation through the use of calibration coefficients (CC). Here, we tested the assumption that CC are independent of dietary fat concentrations by feeding Atlantic pollock ( Pollachius virens ) three formulated diets with very similar FA proportions but different fat concentrations (5–9% of diet) for 20 weeks. CC calculated using FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Future experiments featuring supplemented yeast spiked with lower levels of marker fatty acids (e.g., 0.05%, 0.1%, and 0.5%) should fit this data gap. Similar effects were observed in marine QFASA research (Budge et al., 2020 ), where the diets in many feeding experiments already exceeded the fat levels representative for natural food. Further, as dietary resources in soil are typically low in fat, the rate of de novo fatty acid synthesis is high (Fernando‐Warnakulasuriya et al., 1988 ; Stanley‐Samuelson et al., 1988 ), leading to soil consumer metabolism with very variable CCs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Future experiments featuring supplemented yeast spiked with lower levels of marker fatty acids (e.g., 0.05%, 0.1%, and 0.5%) should fit this data gap. Similar effects were observed in marine QFASA research (Budge et al., 2020 ), where the diets in many feeding experiments already exceeded the fat levels representative for natural food. Further, as dietary resources in soil are typically low in fat, the rate of de novo fatty acid synthesis is high (Fernando‐Warnakulasuriya et al., 1988 ; Stanley‐Samuelson et al., 1988 ), leading to soil consumer metabolism with very variable CCs.…”
Section: Discussionsupporting
confidence: 80%
“…As the QFASA algorithm bases its calculation on the proportion of dietary fatty acids incorporated into the consumers’ lipid signature, factors with impact on this proportion are a prime target to advance the model. While ideally the CCs of a fatty acid should be close to static, several studies have shown CCs vary strongly within the same consumer, when fed on different resources (Magnone et al., 2015 ; Rosen & Tollit, 2012 ) as well as with the fat content of the diet (Budge et al., 2020 ). Similarly, the study focusing on QFASA in soil ecosystems observed variation in CCs between diets (Kühn et al., 2020 ), suggesting the fat content to be particularly important due to the generally low quality of soil food web resources.…”
Section: Introductionmentioning
confidence: 99%
“…Adult wild Atlantic pollock were caught using a commercial long line and transferred to the Aquatron Facility at Dalhousie University. Detailed descriptions of animal care, feeds and experimental design can be found in Budge et al (2020). Briefly, 11 fish were immediately euthanized to serve as initial samples and the remainder were tagged with a passive integrated transponder tag near the dorsal fin.…”
Section: Experimental Fish and Dietsmentioning
confidence: 99%
“…They were then separated into 9 tanks with 12 fish in each tank. Diets were formulated as moist pellets with lipid contents of ~5, 7 and 9% (wwb; referred to as Diets L, M and H, respectively) as described in Budge et al (2020). After pooling all batches of a diet, six samples of each were taken for determination of lipid concentration and FA profile.…”
Section: Experimental Fish and Dietsmentioning
confidence: 99%
See 1 more Smart Citation